A New Memristor-Based 5D Chaotic System and Circuit Implementation. (2nd December 2018) - Wang, Rui; Li, Mingjin; Gao, Zhaoling; Sun, Hui
Abstract : This paper proposes a new 5D chaotic system with the flux-controlled memristor. The dynamics analysis of the new system can also demonstrate the hyperchaotic characteristics. The design and analysis of adaptive synchronization for the new memristor-based chaotic system and its slave system are carried out. Furthermore, the modularized circuit designs method is used in the new chaotic system circuit implementation. The Multisim simulation and the physical experiments are conducted, compared, and matched with each other which can demonstrate the existence of the attractor for the new system.